PENGARUH KEPERCAYAAN MEREK, KEAKRABAN MEREK, DAN PENGALAMAN MEREK TERHADAP KETERIKATAN MEREK PADA KONSUMEN SEPEDA MOTOR YAMAHA DI BANDA ACEH - Ratih Furrahmi, Syafruddin Chan (Departemen Manajemen, 2018)
ABSTRACT The purpose of this study is to determine the influence of brand trust, brand familiarity and brand experience towards brand attachment. The samples used in this study is 132 respondents who have used Yamaha motorcycles for 3 years. The sampling technique used was non probability sampling with purposive sampling method. Multiple Linear Regression was used as a method of analysis to determine the effect of the variables involved.. The results of this study showed that independent variables of brand trust, brand familiarity and brand experience showed a positive and significant influence (sig 0,05) on brand attachment either partially or simultaneously.Keywords: Brand Trust, Brand Familiarity, Brand Experience, Brand Attachment